2004
DOI: 10.1093/jee/97.2.361
|View full text |Cite
|
Sign up to set email alerts
|

Sex Pheromone of the Citrus Mealybug Planococcus citri: Synthesis and Optimization of Trap Parameters

Abstract: A simple synthesis of the pheromone of the citrus mealybug, Planococcus citri (Risso) (Hemiptera: Pseudococcidae), has been developed. Various factors affecting capture of males have been assessed to optimize the trap design and to develop a lure with high efficacy and longevity. Male capture was the same with the racemic and chiral pheromone; technical pheromone (85% purity) was statistically as attractive as pure pheromone (97%). A special formulation was used to determine the actual release rate of the pher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 7 publications
1
19
0
Order By: Relevance
“…2) suggested that this species might be slightly deterred by higher doses/release rates, with the initial release rate of the 25-g dose apparently causing some degree of inhibition. Overall, the effective lifetimes of P. viburni and P. longispinus lures were similar to those reported for male P. ficus, P. citri, and M. hirsutus (12 wk, 16 wk, and 5 mo, respectively) (Millar et al 2002, Zada et al 2004, Zhang and Amalin 2005. These long effective lifetimes of lures will lower costs for growers because lures will need to be changed only every 3Ð 4 mo, or approximately twice a growing season when these mealybug species are most active.…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…2) suggested that this species might be slightly deterred by higher doses/release rates, with the initial release rate of the 25-g dose apparently causing some degree of inhibition. Overall, the effective lifetimes of P. viburni and P. longispinus lures were similar to those reported for male P. ficus, P. citri, and M. hirsutus (12 wk, 16 wk, and 5 mo, respectively) (Millar et al 2002, Zada et al 2004, Zhang and Amalin 2005. These long effective lifetimes of lures will lower costs for growers because lures will need to be changed only every 3Ð 4 mo, or approximately twice a growing season when these mealybug species are most active.…”
Section: Discussionsupporting
confidence: 72%
“…1). Trap catches leveled off as the dose increased, suggesting that male P. longispinus and P. viburni orient and ßy to a source once the pheromone surpasses a threshold concentration (Millar et al 2002, Zada et al 2004. Analogous doseÐresponse trends have been observed with other species such as P. citri and P. ficus (Hefetz and Tauber 1990, Millar et al 2002, Zada et al 2004.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…The P. citri and P. ficus pheromones were prepared as suggested by Zada et al (2004) and by Zada et al (2003), respectively. The pheromone of P. cryptus was donated by Tomonori Arai (Department of Apple Research, NIFTS, Morioka, Japan), prepared as suggested by Nakahata et al (2003).…”
Section: Preparation Of Sex Pheromones For Behavior Testsmentioning
confidence: 99%
“…However, a pheromone critical release value for mass trapping has been obtained for a few species (Hallett et al, 1999;Zada et al, 2002;Zada et al, 2004;Cross et al, 2006). Different authors have reported that high levels of pheromone tend to confuse insects rather than attract them (Jacobson & Beroza, 1964;Zhang & Amalin, 2005).…”
Section: V4 Discussionmentioning
confidence: 99%